2017
DOI: 10.1002/aoc.3999
|View full text |Cite
|
Sign up to set email alerts
|

Sulfamic acid immobilized on amino‐functionalized magnetic nanoparticles: A new and active magnetically recoverable catalyst for the synthesis of N‐heterocyclic compounds

Abstract: Sulfamic acid immobilized on amino‐functionalized magnetic nanoparticles (MNPs/DETA‐SA) was successfully fabricated and characterized using various techniques. Diameters of approximately 15 nm for the MNPs/DETA‐SA were observed from scanning electron microscopy images. The as‐fabricated nanocomposite was applied as an efficient and magnetically reusable catalyst for the synthesis of 2,3‐dihydroquinazoline‐4(1H)‐one and polyhydroquinoline derivatives. All products were obtained in good to excellent yields. Reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…According to previous reports, the XRD pattern of first to third steps shows the standard XRD pattern of crystalline cubic spinel Fe 3 O 4 nanoparticles . XRD pattern of the fourth step and final synthesized compounds, standard XRD pattern of crystalline cubic spinel Fe 3 O 4 nanoparticles in positions of 2θ angles at 30.2°, 35.69°, 43.5°, 53.75°, 57.6° and 63.8° were shown.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…According to previous reports, the XRD pattern of first to third steps shows the standard XRD pattern of crystalline cubic spinel Fe 3 O 4 nanoparticles . XRD pattern of the fourth step and final synthesized compounds, standard XRD pattern of crystalline cubic spinel Fe 3 O 4 nanoparticles in positions of 2θ angles at 30.2°, 35.69°, 43.5°, 53.75°, 57.6° and 63.8° were shown.…”
Section: Resultssupporting
confidence: 55%
“…In the five step, spiro[indoline‐3,4′‐[1,3]dithiine]@Ni (NO 3 ) 2 supported on Fe 3 O 4 @SiO 2 @CPS nanoparticles were synthesized (Scheme ). In the first step, Fe 3 O 4 nanoparticles were synthesized by using the previous method . Coating of Fe3O4 nanoparticles was carried out in the second step using the suggested methods .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shiri et al . also found that sulfamic acid, immobilized on amino‐functionalized magnetic nanoparticles with an average size of 15 nm, is a highly active catalyst for the synthesis of polyhydroquinoline derivatives . As outlined in Scheme , the resulting nanocatalyst (Fe 3 O 4 MNPs/DETA‐SA) was prepared in four steps involving the preparation of Fe 3 O 4 MNPs, Fe 3 O 4 functionalized‐trimethoxysilane, Fe 3 O 4 functionalized‐diethylenetriamine (DETA) and the Fe 3 O 4 MNPs/DETA‐SA.…”
Section: Magnetically Recoverable Nanocatalysts In Synthesis Of Polyhmentioning
confidence: 99%
“…[3][4][5][6][7][8] Despite of a variety of applications for polyhydroquinoline derivatives, very few approaches have been established for the synthesis of these compounds. In recent years, more efficient catalysts have been reported for the synthesis of polyhydroquinolines, such as baker's yeast, [10] Ce(NH 4 ) 2 (NO 3 ) 6 , [11] glycine, [12] grinding, [13] hafnium (IV) bis(perfluorooctanesulfonyl)imide complex in fluorous media, [14] Ni 0.35 Cu 0.25 Zn 0.4 Fe 2 O 4 magnetic nanoparticles (MNPs), [15] Hy-Zeolite, [16] Cu-S-(propyl)-2aminobenzothioate, [17] L-proline and derivatives, [10] metal triflates, [18] molecular iodine, [19] Fe 3 O 4 -adenine-Ni, [20] 4,4′-(butane-1,4-diyl)bis(1-sulfo-1,4-diazabicyclo [2.2.2] octane-1,4-diium)tetrachloride, [21] PTSA, [22] solar thermal energy, [23] MCM-41@Serine@Cu(II), [24] MNPs/DETA-SA, [25] Ni-Cu-Mg Fe 3 O 4 MNPs, [26] ILOS@Fe/TSPP, [27] alginic acid, [28] Ni@IL-OMO, [29] V-TiO 3 [30] and melamine trisulfonic acid. [9] However, this method has some disadvantages like the harsh conditions of the reaction, tedious workup procedure, low yields, use of large quantities of volatile organic solvent and long eaction times.…”
Section: Introductionmentioning
confidence: 99%